Familial risk of psychosis in obsessive-compulsive disorder: Impact on clinical characteristics, comorbidity and treatment response. (December 2022) - Balachander, Srinivas; Thatikonda, Navya Spurthi; Kannampuzha, Anand Jose; Bhattacharya, Mahashweta; Sheth, Sweta; Ramesh, Vinutha; Chandy Alexander, Alen; Muthukumaran, Moorthy; Joseph, Mino Susan; Selvaraj, Sowmya; Ithal, Dhruva; Sreeraj, Vanteemar S.; et al.
Abstract: Background: Family studies in obsessive-compulsive disorder (OCD) indicate higher rates of psychosis among their first-degree relatives (FDRs). However, the etiological and clinical relationships between the two disorders remain unclear. We compared the clinical characteristics and pharmacological treatment response in patients diagnosed with OCD with a family history of psychosis (OCD-FHP), with a family history of OCD (OCD-FHO) and those with sporadic OCD (OCD-S). Methods: A total of 226 patients who met DSM-IV criteria for OCD (OCD-FHP = 59, OCD-FHO = 112, OCD-S = 55) were included for analysis. All patients were evaluated using the Mini International Neuropsychiatric Interview (MINI 6.0.0), Yale-Brown Obsessive-Compulsive Scale (YBOCS), and the Family Interview for Genetic Studies (FIGS). Treatment response was characterized over naturalistic follow-up. Results: The three groups did not differ across any demographic or clinical variables other than treatment response. Patients in the OCD-FHP group were found to have received a greater number of trials with serotonin reuptake inhibitors (SRI) [F (2, 223) = 7.99, p < 0.001], were more likely to have failed ≥2 trials of SRIs (χ 2  = 8.45, p = 0.014), and less likely to have attained remission (χ 2  = 6.57, p = 0.037) Conclusions: We observed that having a relative with psychosis may predispose to treatment resistance in OCD. Further research on the influence of genetic liability to psychosis on treatment response in OCD may offer novel translational leads. Highlights: Familial risk of psychosis (FHP) in OCD was associated with poor treatment outcome. OCD with FHP group received greater number of serotonin reuptake inhibitors (SRIs) trials. Higher SRI resistance, and lower rates of remission were seen in OCD with FHP. No differences in symptoms, comorbidity or demographic profile were seen.